Prognostic significance of occlusion length in recanalized chronic total occlusion lesion: a retrospective cohort study with 5-year follow-up - Bo Xu; Kefei Dou; Yuejin Yang; Lei Song; Tao Tian; Changdong Guan; Lijian Gao; Jiansong Yuan; Fenghuan Hu; Yida Tang; Yongjian Wu; Yinxiao Bai; et al. (BMJ Open)
Objectives This study sought to investigate the relationship between occlusion length and long-term outcomes of patients with recanalised chronic total occlusion (CTO) lesion.Design A retrospective cohort study.Setting Fuwai Hospital, National Center for Cardiovascular Disease, Beijing, ChinaParticipants Consecutive patients with successfully recanalised CTO were included from January 2010 to December 2013.Primary and secondary outcome measures The primary endpoint of the present study was a composite event of all-cause death and myocardial infarction (MI). The secondary endpoints included target lesion revascularisation (TLR) and target vessel revascularisation (TVR).Results A total of 1987 patients were included and 1801 (90.6%) subjects completed 5-year follow-up in this study. Based on occlusion length, the patients were divided equally into two groups: short (length <15 mm, n=957) and long (length ≥15 mm, n=1030) CTO group. Kaplan-Meier survival curve showed no significant difference in the risk of the composite primary endpoint between short and long CTO groups (p=0.242). Receiver operating characteristic curve analysis also established occlusion length ≥15 mm as a cut-off value for predicting TLR and TVR, with an area under the curve of 0.604 (95% CI: 0.569 to 0.638, p<0.001) and 0.605 (95% CI: 0.572 to 0.638; p<0.001). Kaplan-Meier analysis revealed that the risks for TLR (p=0.002) and TVR (p=0.002) were higher in a patient with long CTO lesion. Multivariate Cox analysis also identified long CTO lesion as an independent predictor of TLR (HR: 1.539, 95% CI: 1.033 to 2.293; p=0.034) and TVR (HR: 1.476, 95% CI: 1.012 to 2.151; p=0.043).Conclusion Patients with long CTO lesion did not show a higher risk of death and MI after recanalisation, but had higher risks of TLR and TVR. Lesion with occlusion length ≥15 mm should be under close surveillance for restenosis after recanalisation.